Research Progress on Superheated Steam Pretreatment in Oil Processing - ZHU Miaomiao, LIU Yuan, NIU Jiayu, ZHANG Ruru, YU Miao, XIE Mengxi, XIE Liangliang, GUO Hongyan, ZHANG Tao, ZHENG Liyou (Shipin Kexue)
With its advantages of being oxygen free, highly efficient, safe, and energy-saving and environment-friendly, superheated steam (SHS) technology is gradually gaining attention in the field of oil processing. SHS pretreatment can improve the microstructure of oilseeds, increase oil yield, promote the generation of flavor compounds, and enhance the oxidative stability of oil. This article briefly describes the SHS system with respect to its principle, advantages and limitations, and summarizes recent progress in the application of SHS pretreatment technology in the field of oil processing at home and abroad (including sterilization, stabilization and baking). Furthermore, this paper presents a systematic review of its impact on the physicochemical properties (such as oil yield, water content, microstructure, enzymatic activity, and elimination of harmful microorganisms such as bacteria and fungi), physicochemical indicators (such as color, oxidation indicators, and flavor compounds), nutritional indicators (trace lipid concomitants such as tocopherols and flavonoids), and safety indicators (acrylamide and polycyclic aromatic hydrocarbons) of oil. Although SHS pretreatment technology has received much attention in the field of oil processing, there are still some urgent problems that need to be solved. This paper proposes possible solutions for these problems. This review aims to provide a reference for further research and application of SHS pretreatment technology in the field of oil processing.